THE INFLUENCE OF PRODUCT QUALITY AND PRICE PERCEPTION ON MINISTRY CUSTOMER DECISION AT PT. LIFELONG LEARNING (MULTIMATICS) - Vika Nur Adzni; Muchsin Saggaff Shihab (Sean Institute, 2023)
Customer satisfaction is one of the priorities that needs to be maintained because it is one of the important factors to increase competitiveness. this study uses a sample collections technique based on five agencies, where each agency receives twenty respondents US a sample and uses a purposive sampling technique in which the researcher has planned the respondents who have purchased products at PT. Lifelong Learning ( Multimatics ). Data collections in this study using a questionnaire with a sample of 100 respondents. The results of this study have a positive and significant effect on product quality and price perceptions on ministries customer satisfaction at PT. Lifelong Learning ( Multimatics ). this means that product quality and price perception affect 63.2% of customers satisfaction, while the remaining 36.8% is influenced by other variables that are not examined in this study.